2022
DOI: 10.3389/fnut.2022.1060783
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic potentials of tea catechins

Abstract: Catechins are a cluster of polyphenolic bioactive components in green tea. Anticarcinogenic effects of tea catechins have been reported since the 1980s, but it has been controversial. The present paper reviews the advances in studies on the anticarcinogenic activities of tea and catechins, including epidemiological evidence and anticarcinogenic mechanism. Tea catechins showed antagonistic effects on many cancers, such as gynecological cancers, digestive tract cancers, incident glioma, liver and gallbladder can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 222 publications
0
11
0
Order By: Relevance
“…Catechins, in turn, have been shown to inhibit tumorigenesis, tumor growth, cancer cell invasion and tumor angiogenesis by inhibiting the induction of proangiogenic factors [54]. Several in vitro cell experiments and in vivo animal experiments have shown that catechins have a strong anticarcinogenic effect and effectively suppress the metastasis and invasion of various cancer cells [55]. It should be noted that the flower extracts of wild plants also show good cytotoxic activity against cancer cells, with no significant damaging effects on control cells, especially at 24 h, but the best ratio (cancer cell cytotoxic activity/no harm to healthy cells) remains attributed to the cultivated flower extract at 48 h at a dosage of 500 µg/mL for the HT-29 and HeLa tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins, in turn, have been shown to inhibit tumorigenesis, tumor growth, cancer cell invasion and tumor angiogenesis by inhibiting the induction of proangiogenic factors [54]. Several in vitro cell experiments and in vivo animal experiments have shown that catechins have a strong anticarcinogenic effect and effectively suppress the metastasis and invasion of various cancer cells [55]. It should be noted that the flower extracts of wild plants also show good cytotoxic activity against cancer cells, with no significant damaging effects on control cells, especially at 24 h, but the best ratio (cancer cell cytotoxic activity/no harm to healthy cells) remains attributed to the cultivated flower extract at 48 h at a dosage of 500 µg/mL for the HT-29 and HeLa tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Flavanols are mostly found in variety of foods, including apples, pears, legumes, tea, cocoa, and wine. 95 NG from grapefruits and HP from oranges are the two most important flavanones. 96 Prenylated flavanones, furanoflavanones, pyranoflavanones, and benzylated flavanones, for example, have distinct substitution patterns, resulting in many substituted derivatives in this subgroup.…”
Section: Classification Of Various Polyphenols and Their Role In Canc...mentioning
confidence: 99%
“…Flavanols are composed of simple monomers (catechins), which consist of epicatechin, epigallocatechin (EGC), EGCG, and polymers and/or oligomers, the latter two of which are identified as pro-ACDs or condensed tannins. Flavanols are mostly found in variety of foods, including apples, pears, legumes, tea, cocoa, and wine . NG from grapefruits and HP from oranges are the two most important flavanones .…”
Section: Classification Of Various Polyphenols and Their Role In Canc...mentioning
confidence: 99%
“…However, many epidemiological studies have not yielded constant or conclusive results on the health benefits of tea consumption in humans. For example, EGCG has shown anticancer effects both on cultured cancer cells and in mouse tumor models with strong evidence (Li, Liu, et al., 2022), but there are no clear conclusions in humans. The anticancer effects of EGCG are still controversial in human studies at present.…”
Section: Challenges and Future Directions For Stpfcsmentioning
confidence: 99%